Contribution of NEO Modernism Thoughts on Islamic Thoughts in Indonesia - Annai Saburi; Hasan Bakti Nasution; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of the study is to find out the contribution of NEO modernism trought on Islamic trough in Indonesia. This result of the study is Islamic Civilization" in this case, especially Nurcholish Madjid, considers that Islamic rationalism, which in the classical Islamic tradition emerged in the Mu'tazilite theology and Al-Kindi to Ibn Rushd's theology, then systematically became the rational theology of Muhammad Abduh. Basically Hellenistic, because that is not an Islamic genuin. Theological thought and Rational philosophy according to Islamic circles This civilization was built from the construction of Greek theories (especially Aristotle), which from an Islamic point of view, is actually quite problematic, because it is too Rational. The weakness of this Islam, according to the circles of 'Islamic Civilization because they lack in providing an equilibrium in religious life, which is practical and direct to the daily appreciation of God.